2008
DOI: 10.1021/je800433r
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Solubility in the Homologous 1-Alkyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide Family

Abstract: The high-pressure phase behavior of the binary system CO 2 + 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide was determined experimentally by a synthetic method. Bubble points were measured for mixtures of various carbon dioxide concentrations within a temperature and pressure range of (310 to 450) K and (0.5 to 14) MPa, respectively. The results were compared with solubility data obtained by three other research laboratories using different phase equilibria measuring techniques, and good agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 39 publications
8
84
0
Order By: Relevance
“…It was observed that the reaction time reduction from 6 up to 2 h (entry [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], provided a decreases in yield, curiously the increase in reaction time from 6 to 8 h (entry 4-21) decreases the yield. The reaction time of 6 h was ideal for this the system.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the reaction time reduction from 6 up to 2 h (entry [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], provided a decreases in yield, curiously the increase in reaction time from 6 to 8 h (entry 4-21) decreases the yield. The reaction time of 6 h was ideal for this the system.…”
Section: 10mentioning
confidence: 99%
“…11,15 Regarding CO 2 capture, the imidazolium cations allied to fluoroalkyl anions stand as very effective systems for CO 2 absorption. 17,18 Nevertheless, in relation to the reaction of CO 2 conversion in cyclic carbonates, the results reported in the literature are contradictory in respect to the activity of ionic liquids combined to fluoroalkyl anions.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results found in the literature for solubility of CO 2 in the ionic liquids [C n -mim][Tf 2 N] (n=2, 4,6,8) show that CO 2 gives very high solubility in ionic liquids at lower pressures, while the equilibrium pressure increases very steeply at higher concentrations of CO 2 . The solubility of CO 2 in the ionic liquids decreases with an increase in temperature.…”
Section: Resultsmentioning
confidence: 98%
“…To select an efficient ionic liquid for use as a gas separation medium, it is necessary to know the solubility of the gas in ionic liquid phase. Thus, phase equilibrium properties of carbon dioxide in ILs are required [2][3][4][5][6]. These properties must be either experimentally obtained or semi-empirically correlated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation